Eco-friendly aqueous spinning of robust and porous carbon nanotube/graphene hybrid microelectrodes: The graphene oxide size effect - Kang Cheng; Munan Lu; Zeyuan Wang; Lingzhi Cheng; Xinrong Jiang; Jiangtao Di; Shuxuan Qu; Weibang Lyu (Materials & Design, 2024)
An eco-friendly, cost-effective, and scalable aqueous spinning of robust and porous hybrid fibers consisting of carbon nanotubes (CNTs) and graphene has been developed. We focus on the design of nanoarchitecture within CNT fibers involving the precise control of CNT bundle size and alignment, porosity, and the interaction between CNTs and Graphene. The effect of graphene oxides (GO) sizes on the quality of CNT/GO aqueous dispersions and the structures/properties of the as-spun fibers was investigated, and nano-sized GO was found to be most effective in reducing CNT bundle size, improving CNT alignment, and strengthening the fibers. After high-temperature treatment, the specific strength and specific conductivity of these CNT/graphene hybrid fibers reached to 1.02 N/tex and 1202.01 S m2/g, which were 7.39 and 1.21 times higher than those of pure CNT fibers. Meanwhile, the CNT/graphene hybrid fibers also have a high specific capacity of 168 F g−1. The combination of high mechanical, electrical, and electrochemical performances makes the CNT/graphene hybrid fibers promising materials for wearable electronics.